(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the semantic functions of speech sounds and phonemes, exploring their role in creating and differentiating meaning in language. Phonemes, as the smallest sound units, lack inherent meaning but enable semantic distinction through their contrastive features. By comparing phonemes in different linguistic contexts (e.g., English and Japanese), the article illustrates how sound contrasts are fundamental to language specificity. Furthermore, it examines allophones, phonesthemes, and prosody, which, while not altering word meanings directly, contribute to social, emotional, and symbolic layers in communication. Prosody, through intonation and stress patterns, exemplifies how phonemes participate in conveying emotions and emphasis, adding richness to spoken language. This nuanced analysis underscores the interconnectedness of phonology and semantics, showing how phonemes serve as a bridge between sound and meaning, thus enhancing the depth and versatility of human language. This exploration is valuable for those interested in linguistics, cognitive science, and language acquisition, as it highlights the phonemic foundations of communication and their implications for understanding human thought, culture, and interaction.